2009
DOI: 10.1074/jbc.m901104200
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-sensitive Regulation of TMS1/ASC by the Ets Factor, GA-binding Protein-α

Abstract: Epigenetic silencing involving the aberrant DNA methylation of promoter-associated CpG islands is one mechanism leading to the inactivation of tumor suppressor genes in human cancers. However, the molecular mechanisms underlying this event remains poorly understood. TMS1/ASC is a novel proapoptotic signaling factor that is subject to epigenetic silencing in human breast and other cancers. The TMS1 promoter is embedded within a CpG island that is unmethylated in normal cells and is spanned by three DNase I-hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…Additionally, Lucas et al showed that GABPA was selectively enriched at HS2 in human cells, and its occupancy was inversely correlated with CpG island methylation of the TMS1 gene [39]. These results suggest the epigenetic regulation of GABPA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lucas et al showed that GABPA was selectively enriched at HS2 in human cells, and its occupancy was inversely correlated with CpG island methylation of the TMS1 gene [39]. These results suggest the epigenetic regulation of GABPA expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the activity of each of these transcription factors is affected by the presence or absence of DNA methylation (3,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). For some of these transcription factors, the databases contained multiple identical position weight matrices.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction protocol began with a 3 min hot start at 95°C and followed with cycles of 95°C, 10 s; 55°C, 60 s. Melt curve analysis verified a single product. Relative quantities were calculated, standardized by comparison to 18 S rRNA (small ribosomal subunit) (23). Primers used were as follows: STRAD␣ (forward-GCCAT-GTCCCCTTTAAGGAT, reverse-TCATGGTCAGCTCCT-CAGC), 18 S (forward-GAGGGAGCCTGAGAAACGG, reverse-GTCGGGAGTGGGTAATTTGC).…”
Section: Methodsmentioning
confidence: 99%